1982
DOI: 10.1111/j.1365-2141.1982.tb03910.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DA monoclonal antibodies inhibit the proliferation of normal and chronic granulocytic leukaemia myeloid progenitor cell

Abstract: We studied the capacity of murine monoclonal antibodies with HLA-DR specificity to inhibit the proliferation in vitro of erythroid (BFU-E and CFU-E) and granulocyte-macrophage (CFU-GM) progenitor cells in normal bone marrow and the blood of patients with chronic granulocytic leukaemia (CGL). Two IgG2 antibodies (CA 2.06 and L243) inhibited the proliferation of normal BFU-E and CFU-GM at relatively high dilution; a third antibody, DA2, had no effect on either progenitor cell. A complement-fixing monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…This suggests that the few nonleukemic HLA-DR positive cells did not contribute greatly to the number of cells lysed. Secondly, the agar culture results also show complement-dependent cytotoxicity on stem cells (Table 7), agreeing with the results of Goldman et al [7]. It seems probable that the Ia antigen found on committed but not on uncommitted stem cells is partially responsible for this effect.…”
Section: Cytotoxie Effects On Normal Marrow Eellssupporting
confidence: 82%
“…This suggests that the few nonleukemic HLA-DR positive cells did not contribute greatly to the number of cells lysed. Secondly, the agar culture results also show complement-dependent cytotoxicity on stem cells (Table 7), agreeing with the results of Goldman et al [7]. It seems probable that the Ia antigen found on committed but not on uncommitted stem cells is partially responsible for this effect.…”
Section: Cytotoxie Effects On Normal Marrow Eellssupporting
confidence: 82%
“…28 The humanized mouse anti-human EGFR chimeric IgG1 mAb, cetuximab (Erbitux, ImClone Systems Incorporated, New York, NY and Bristol-Myers Squibb Company, Princeton, NJ), and rituximab, a humanized mouse anti-human chimeric CD20-specific IgG1 isotype mAb control mAb (Roche, Basel, Switzerland) were purchased. An irrelevant specificity control human IgG2 mAb was purchased from BD Biosciences (Rochester, NY).…”
Section: Methodsmentioning
confidence: 99%
“…In this respect CEW-GEMM in CGL seem to differ from CFU-GM. In previous studies we could detect no important difference in the degree to which DR antigen was expressed on the surface between CGL and normal CFU-GM (19); others however have reported that CGL CFU-GEMM were inhibited to a lesser degree by antibody with DR specificity and that this difference paralleled their reduced sensitivity to inhibition by prostaglandin E When normal nucleated marrow cells were first incubated in liquid culture and then assayed after various periods of incubation for myeloid progenitor cell numbers, CFU-GM numbers at first increased and then declined; BFU-E and CFU-GEMM numbers declined steadily during liquid culture. When normal marrrow cells (23).…”
Section: Discussionmentioning
confidence: 65%
“…Results of studies using immunofluorescence techniques and complement-mediated cytotoxicity with conventional and monoclonal antibodies have shown that singlelineage committed myeloid progenitors (CFIJ-GM and BFU-E) express HLA-A, B and DR antigens on their membranes (12)(13)(14)(15)(16)(17)(18)(19). Whether or not the pluripotential haemopoietic stem cell carries HLA surface determinants is not yet established but the results of our studies, as well as those of others, suggest that the proliferation of CFU-GEMM can be completely or almost completely inhibited by prior incubation of cells with cytotoxic antibodies with DR specificity (20,21).…”
Section: Discussionmentioning
confidence: 99%